Characterization of CuO-Kaolin Solids Used for Co-oxidation - Amin, R.S.; Attia, A.A.; Samra, S.E.; Hassan, N.A.; Selim, M.M.; Fouda, M.F.R. (Asian Journal of Chemistry, 2010)
Six samples of copper oxide/kaolin were prepared by impregnating kaolin with solution containing different concentrations of Cu-nitrate. The obtained solids were thermally treated at different temperatures. The thermal products were characterized by XRD-analysis and were tested in the oxidation of carbon monoxide. The results of X-ray investigation revealed that, supported metal oxide on the surface of kaolin appeared as crystalline oxide in the X -ray diffracto gram. Solid-solid interaction occurred between the oxide and the decomposition products of kaolin yielding aluminate CuAl2O4 and CuAl2O4- Al2O3 solids solution. The prepared solids were tested in the oxidation of carbon monoxide. The results of the effect of calcination temperature on the activity revealed that catalysts activated at 350ºC were more active than those activated at 550 or 750ºC. The low activity may be attributed to the interaction between CuO and the thermal decomposition products of kaolin and/or sintering of the heated solid. The catalytic activity increased with increasing the metal oxide content in the catalyst and also with increasing the reaction temperature. The presence of oxygen (air) prevents the appearance of monovalent copper or metallic copper. This is because the reduced forms of copper are oxidized as fast as they formed.